Digital Transformation in MSME: Trends and Opportunities - Pradeep Mamgain, (AG Volumes, 2025)
The Indian economy is dominated by the Micro, Small, and Medium Enterprise (MSME) sector, which makes a substantial contribution to GDP, merchandise exports, and the nation's overall growth. Digital transformation is currently a major factor in global economic development, especially for MSMEs (micro, small, and medium-sized enterprises). The opportunities and challenges of MSME digital transformation, MSMEs' digital transformation trends, and methods for accelerating MSMEs' digitization were all covered in this article. This article concluded that digital transformation enables MSMEs to improve efficiency, reduce costs, and expand market reach through technologies like cloud computing, e-commerce, digital payments, and analytics. Despite challenges such as limited resources and low digital awareness, government initiatives and emerging trends like ONDC and automation support adoption. Integrating digital tools across business functions can significantly enhance MSME competitiveness and long-term sustainability